2021
DOI: 10.1523/eneuro.0028-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Power in Fronto-Parietal Theta EEG Linked to Impaired Attention-Sampling in Adult ADHD

Abstract: for data gathering; Otto Lappi, Alina Leminen and Eeva Palomäki for comments to the manuscript. Conflict of InterestAuthors report no conflict of interest 15. Funding sources This work was supported by the TEKES (presently Business Finland) grant number 440078.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…This finding was confirmed by MPRAGE, which supported a reduction in the volume of the parietal lobes (Jacobson et al, 2018). Furthermore, EEG showed decreased parietal lobes activity (Cowley et al, 2020). Finally, interventional studies confirm these findings.…”
Section: Bilateral and Central Parietal Lobesupporting
confidence: 60%
See 1 more Smart Citation
“…This finding was confirmed by MPRAGE, which supported a reduction in the volume of the parietal lobes (Jacobson et al, 2018). Furthermore, EEG showed decreased parietal lobes activity (Cowley et al, 2020). Finally, interventional studies confirm these findings.…”
Section: Bilateral and Central Parietal Lobesupporting
confidence: 60%
“…Based on EEG results, less theta rhythm and more α rhythm are shown during the control of irrelevant visual stimuli (Bush et al, 2013;Cowley et al, 2020). However, boosting the right PPC through tDCS did not alter cognitive control (Salehinejad et al, 2020), so it is likely that increased right parietal cortex activity depends on increased left parietal cortex activity during irrelevant stimulus inhibition, indicating the role of bilateral parietal lobes in cognitive control (Berberat et al, 2021).…”
Section: Bilateral and Central Parietal Lobementioning
confidence: 99%
“…LRTCs are a characteristic feature of behavioral performance and healthy brain activity 59 while their aberrancies are a characteristic feature of many brain diseases. [37][38][39][40][41][42][43][44][45] We investigated This shows that in ADHD, oscillation dynamics is altered across time scales from seconds to minutes, in addition to the previously found sub-second time scale abnormalities in alpha band for adult, 21,27,29 adolescent 60,61 and child ADHD patients, 30 and in theta- 62 and gamma-bands for adult ADHD. 20 These results are also in line with a recent study reporting intrinsic temporal variability in functional connectivity in ADHD patients 63 and show that aberrant temporal dynamics is also a characteristic of local neuronal processing.…”
Section: Discussionmentioning
confidence: 96%
“… Cavaliere et al (2018) also observed that patients have predominant posterior theta activity. Theta activity is generally considered to reflect fundamental cognitive functions ( Biel et al, 2022 ; Cowley et al, 2022 ). An association between increased theta connectivity and cognitive dysfunction has been reported in some diseases such as Alzheimer’s disease, Parkinson’s disease, and schizophrenia ( Andreou et al, 2015 ; Iyer et al, 2020 ; Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%